Hysteroskopischer Wegweiser für Gynäkologen - Römer, T. (Thomas) (Frauenärztliche Taschenbücher., 2008)
The diagnostic investigation of menstrual dysfunction and sterility is a routine part of gynecological practice. Hysteroscopy can expand the spectrum of diagnostic possibilities. The 2nd revised edition of this handbook aims to familiarise the gynecologist with diagnostical hysteroscopy. About 100 colour plates facilitate the acquisition of this technique as well as the correct assessment of findings. The book is conceived for newcomers to hysteroscopy and should contribute to the further establishment of this method.